In the context of superstring compactification on a 6-manifold which admits a covariantly conserved spinor $\eta$, which we normalize so that $\eta^{\dagger} \eta = 1$, I am trying to show that the almost complex structure

$$J_m^{\,\,n} = -i \eta^{\dagger} \gamma_{m}^{\,\,n}\gamma \eta$$

satisfies $$J_m^{\,\,n} J_n^{\,\,p} = -\delta_m^p. $$

Here $\gamma_{mn} = \gamma_{[mn]}$ and $\gamma$ is the chirality operator. I'm aware that the Fierz rearrangement identity should be used,

$$\chi_\alpha \zeta \xi + \zeta_\alpha \xi \chi + \xi_{\alpha} \chi \zeta= 0$$

but I cannot show $J^2 = -1$, and would appreciate any help.

Attempt. Take $\eta$ to be real and to have chirality $+1$ so $\gamma \eta = \eta$. Now, with some spinor indices explicit, $$J_m^{\,\,n} J_n^{\,\,p} = - \eta_{\alpha} (\gamma_m^{\,\,n}\eta)^{\alpha} \eta(\gamma_{n}^{\,\,p}\eta)$$ $$ = \eta_{\alpha}\eta^\alpha (\gamma_{n}^{\,\,p}\eta)(\gamma_m^{\,\,n}\eta)+ \eta_\alpha (\gamma_{n}^{\,\,p}\eta)^\alpha(\gamma_m^{\,\,n}\eta)\eta $$ $$ = 1 \cdot (\gamma_{n}^{\,\,p}\eta)(\gamma_m^{\,\,n}\eta)+ \eta_\alpha (\gamma_{n}^{\,\,p}\eta)^\alpha(\gamma_m^{\,\,n}\eta)\eta.$$ Perhaps there is some gamma matrix algebra which would help me simplify this to $-\delta_m^{\,\,p}$.

(Ref: "Vacuum Configurations for Superstrings", Candelas et al. 1985)

  • $\begingroup$ Question: are $\chi,\zeta,\xi$ are arbitrary spinors in your Fierz identity formula? If we take $\chi = \zeta = \xi = \eta$, it looks like the Fierz identity reduces to $3\eta_\alpha = 0$ which looks weird? $\endgroup$
    – chichi
    Aug 16 '19 at 2:25

We have $SO(6)=SU(4)$ so a chiral spinor will be in the fundamental of $SU(4)$: $\eta^I$, $I=1,...,4$. You are imposing an additional restriction to $\eta^{I}$:

$$ \bar\eta_{I}\eta^{I}=1 $$

where $\bar\eta_{I}=(\eta^{I})^*$.

Than you propose that

$$ J_m^n = -i \bar\eta_{I}(\sigma_{m}^{n})^I\,_{J}\eta^{J} $$

defines an almost complex structure. So you need to check that $J_m^nJ_n^p=-\delta_m^p$, which is the same as checking that

$$ (\sigma_{n}^{p})^{(I}\,_{(J}(\sigma_{m}^{n})^{K)}\,_{L)}=\sigma_{[n}^{(I|M}\bar\sigma_{p]M(J|}\sigma_{[m}^{|K)N}\bar\sigma_{n]N|L)}=\delta^{I}_{J}\delta^{K}_{L}\delta_{m}^{p} $$

The indices $IK$ and $JL$ are symmetrized because they are hitting pairs of equal bosonic spinors. Note that the vectorial indices can be lowered and raised since we are dealing with $SO(6)$, and the metric $\delta_{mn}$ is a Kronecker delta.

In order to check this identity you are going to need to know the $SO(6)$ bi-spinor decomposition:

$$ \delta_K^I\delta_L^J=\frac{1}{4}\sigma_m^{IJ}\bar\sigma^m_{KL} +\frac{1}{4}\frac{1}{3!\times 2}\sigma_{mnp}^{IJ}\bar\sigma^{mnp}_{KL} $$

Since $\sigma_m^{IJ}=-\sigma_m^{JI}$, we have that $\sigma_{mnp}^{IJ}=+\sigma_{mnp}^{JI}$, we have:

$$ \delta_K^{(I}\delta_L^{J)}=\frac{1}{4}\frac{1}{3!\times 2} \sigma_{mnp}^{IJ}\sigma_{KL}^{mnp} $$

$$ \delta_K^{[I}\delta_L^{J]}=\frac{1}{4}\sigma_m^{IJ}\bar\sigma^m_{KL} $$

Since $(\sigma^{m}\sigma^{npq}\sigma^{m})=0$ by the anti-commutation relations, we can use the equations above to show that:

$$ \bar\sigma_{K(L}^{m}\bar\sigma_{I)J}^{m}=0\implies\varepsilon_{IJKL}=\frac{1}{2}\bar\sigma_{KL}^{m}\bar\sigma_{IJ}^{m}\implies \bar\sigma_{IJ}^{m}=\frac{1}{2}\varepsilon_{IJKL}\sigma^{KL}_m $$

And similarly

$$ \varepsilon^{IJKL}=\frac{1}{2}\sigma^{KL}_{m}\sigma^{IJ}_{m}\implies \sigma^{IJ}_{m}=\frac{1}{2}\varepsilon^{IJKL}\bar\sigma_{KL}^m $$

This is all you need in order to prove that $J_m^nJ_n^p=-\delta_m^p$, just expand the four terms in $\sigma_{[n}^{(I|M}\bar\sigma_{p]M(J|}\sigma_{[m}^{|K)N}\bar\sigma_{n]N|L)}$ that comes from the antisymmetrization in $np$ and $mn$, and apply the identities above for each pair of sigma matrices with vectorial indices contracted.

Hint: at the end, because of the symmetrization in $IK$ and $JL$, most of the terms in $(\sigma_{n}^{p})^{(I}\,_{(J}(\sigma_{m}^{n})^{K)}\,_{L)}$ cancel, and the only term left is proportional to:

$$ (\sigma_{p}\sigma_{m}+\sigma_{m}\sigma_{p})^{(I}\,_{(L}\delta_{J)}^{K)} $$

and in my conventions the anti-commutation relation between gamma matrices are

$$ (\sigma_{m}\sigma_{n}+\sigma_{n}\sigma_{m})^{I}\,_{J}=-2\eta_{mn}\delta_{J}^{I} $$


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.